HUBUNGAN PENGETAHUAN, WAKTU PENGAMBILAN KEPUTUSAN DENGAN KETEPATAN PENANGANAN STROKE PRA RUMAH SAKIT - Gadur Blasius; Yoany Maria Vianney Bita Aty; Pius Selasa; Aben B.Y.H.Romana (Bajang Institute, 2024)
Stroke, a leading cause of death and disability globally, poses significant challenges in timely pre-hospital care. This study, conducted in Kupang City using a cross-sectional quantitative method, involved 300 respondents selected through multistage random sampling. The study aimed to assess the relationship between community knowledge and perceptions in handling stroke emergencies. The largest respondent group was aged 25-45 years (36.3%), with a majority being male (55.0%) and having a high school education (55.3%). Despite 68.3% never receiving stroke-related information, knowledge did not significantly affect pre-hospital care accuracy (p=0.814). However, a significant relationship was found between the timeliness of family decision-making and pre-hospital care accuracy (p=0.001). The study highlights that while knowledge is important, factors like accessibility to health services and practical experience play a more critical role. Swift decision-making in bringing stroke patients to the hospital is vital for effective treatment. This underscores the importance of public health education and interventions to enhance community response to stroke emergencies.